Brittle Fracture Model Parameter Estimation for Irradiated BCC Material through Dislocation Based Crystal Plasticity Model (Fracture and Structural Integrity, 2019)
Radiation effects lead to significant reduction in ductility during the life of the components used in nuclear reactors. Sharp change in fracture toughness at lower temperature in Body Centered Cubic (BCC) materials as compared to Face Centered Cubic (FCC) materials is a major concern restricting their application in nuclear reactors in spite of having better thermal properties, excellent resistance to helium embrittlement and void swelling under higher dpa levels. In the present paper such strong temperature dependence of strain rate and flow stress in BCC materials is investigated numerically for both non-irradiated and irradiated conditions. The BCC materials subjected to radiation would undergo embrittlement which raises the ductile to brittle transition (DBT) temperature up to or above the room temperature. In view of dislocations mobility being a fundamental property to determine the plastic behavior, a dislocations based material model is proposed which has a physical rather than phenomenological basis. This material model accounts for both thermally activated and athermal regime dislocation mobilities in BCC materials and is capable of predicting the effect of irradiation induced defects on the mobility of the dislocations which in turn directly affect the behavior of such materials. The relative change in stress field due to presence of irradiation defects in comparison to non-irradiated case provides a valuable input for brittle fracture model to develop advanced materials for nuclear application.
Keywords: Irradiation defects; Crystal plasticity; Dislocation mobility